Dignidade da pessoa humana, coisificação na modernidade líquida e acesso à justiça - Lewin, Augusto Miranda (2018)
It addresses the human behavior found in the Liquid Modernity of Zygmunt Bauman, focusing on the analysis of the individual consumer, the historicity of the dignity of the human person and the achievements of people through Law, while society does not stop going through several behavioral changes intimately linked to modern life. The theme of the humanization of consumer objects in the face of human reification is also present as a way of punctuating the social crisis of people's identity, but also through access to justice, the right means a way to rescue the dignity of the person In a consumer society